Kejadian anemia, pola menstrual bleeding dan status nutrisi pada siswi di SMAN 3 Salahutu, Maluku Tengah - Rosdiana Mus; Mutmainnah Abbas; Dylan tamalsir; Presli Golving Siahaya (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background: Anemia is a nutritional problem with a high incidence. Anemia is characterized by decreased hemoglobin (Hb) levels below normal. Adolescents are one of the groups at high risk of anemia because they experience menstrual cycles every month. Irregular menstrual bleeding patterns and nutrition can also be risk factors for anemia. Prevention of anemia is necessary to reduce the risk of anemia.Objectives: To determine the incidence of anemia, menstrual bleeding patterns, and nutritional status in female students at Salahutu Senior High School, Central Maluku.Methods: The study was descriptive and observational with a cross-sectional design. The study was conducted in October-December 2022 at Senior High School 3 Salahutu, Central Maluku. The number of subjects was 142, who met the inclusion criteria with an age range from 14 to 19 years. The research variables consisted of checking Hb levels using digital hb, and anthropometric measurements, namely BMI, and filling out questionnaires. Data analysis in this study used the Chi-square test at the 95% significance level.Results: The results showed that the number of age categories 16 years with the highest number of subjects, 35,9%, and underweight IMT category as much as 59,2%. The results of the anemia hemoglobin examination were 7,7%. The age of menarche is mainly at the age of 13 years 34,5%, and based on the length of menstruation, 3-5 days as much as 66,9% and 5-7 days as much as 29,6% with a menstrual cycle of 21-28 days as much as 59,9%. There was no relationship between nutritional status and duration of menstruation (p = 0,648) and Hb levels (p = 0,552). There is a relationship between nutritional status and menstrual cycle (p = 0,020).Conclusion: There is no relationship between nutritional status and duration of menstruation and Hb levels, but there is a relationship between nutritional status and menstrual cycle.